2018
DOI: 10.1016/j.bone.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Variant BMP receptor mutations causing fibrodysplasia ossificans progressiva (FOP) in humans show BMP ligand-independent receptor activation in zebrafish

Abstract: The large majority of cases of the autosomal dominant human disease fibrodysplasia ossificans progressiva (FOP) are caused by gain-of-function Arg206His mutations in the BMP type I receptor ACVR1 (ALK2). The Arg206His mutation is located in the GS domain of the type I receptor. This region is normally phosphorylated by the BMP type II receptor, which activates the type I receptor to phosphorylate its substrate, the signal transducer Smad1/5/8. A small subset of patients with FOP carry variant mutations in ACVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 52 publications
(76 reference statements)
4
32
0
Order By: Relevance
“…While wild-type embryos formed a gradient of pSmad1/5 expression that peaks ventrally and decreases dorsally ( Figure 2a ; Mucha et al, 2018 ), Acvr1l-KD embryos lacked detectable pSmad1/5 signal ( Figure 2a’ ). The mean nuclear pSmad1/5 fluorescence of Acvr1l - KD embryos was significantly decreased compared to WT embryos ( Figure 2h ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While wild-type embryos formed a gradient of pSmad1/5 expression that peaks ventrally and decreases dorsally ( Figure 2a ; Mucha et al, 2018 ), Acvr1l-KD embryos lacked detectable pSmad1/5 signal ( Figure 2a’ ). The mean nuclear pSmad1/5 fluorescence of Acvr1l - KD embryos was significantly decreased compared to WT embryos ( Figure 2h ).…”
Section: Resultsmentioning
confidence: 99%
“…The zebrafish embryo is an excellent genetically tractable in vivo vertebrate model for investigating the signaling mechanism of the ACVR1-FOP receptor ( Shen et al, 2009 ; Mucha et al, 2018 ). In the early zebrafish embryo, BMP acts as a morphogen to pattern the dorsoventral (DV) axis in a process that is conserved throughout the animal kingdom ( Zinski et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ligand-independent signaling, increased SMAD1/5 activation, enhanced chondrogenic and osteogenic properties in different cellular models, and a reduction in FKBP12 binding were also observed for the L196P, Q207E (GS domain) and G356D (kinase domain) substitutions [ 18 , 19 , 20 , 21 ]. Moreover, in vivo studies in zebrafish embryos demonstrated that G356D/W/R substitutions also enhanced the SMAD1/5 signaling and induced embryo ventralization with loss of dorsal cell fate markers, as observed for the R206H mutation [ 22 ]. The activation state of the different mutants is not exactly the same but they are still BMP-responsive and maintain the ability to be down-regulated by known BMP inhibitors such as regulatory SMAD6 and 7, over-expression of FKBP12 or pharmacological treatment with known inhibitors of the signaling such as dorsomorphin and LDN193189 [ 18 , 20 , 21 ].…”
Section: Translating the Results Of Basic Research Into The Develomentioning
confidence: 99%
“…Another excellent example for the use of phenologs in modeling pediatric disorders is fibrodysplasia ossificans progressiva (FOP). In-depth knowledge about the molecular mechanism of early dorso-ventral (DV) patterning in zebrafish development, including the phenotype of ventralized embryos, has been helpful both in the identification of the causative mutations of FOP [ 63 , 64 ] and that of putative drugs [ 142 ].…”
Section: Modeling Disease With Homologs and Phenologsmentioning
confidence: 99%